A Knowlegde PENGETAHUAN, SIKAP DAN PERILAKU IBU HAMIL SELAMA PANDEMI COVID-19: PENGETAHUAN, SIKAP DAN PERILAKU IBU HAMIL SELAMA PANDEMI COVID-19 - Elka Halifah; Mariatul Kiftia; Darmawati Darmawati; Aida Fitri; Mira Rizkia (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2023)
Pregnancy is a physiological process of a woman to continue heredity. This study aimed to examine pregnant women's characteristics in carrying out their pregnancy during a pandemic in Aceh Barat Daya, Aceh. Research Method: This type of research is descriptive with a Cross-Sectional Design approach. The sample in this study was 124 pregnant women as respondents using the Snowball Sampling selection method. Data analysis was carried out using statistical tests using SPSS. The results showed that 86.7% of pregnant women lived in Aceh Barat Daya, the age of pregnant women was 26-30 years of 44.3%, the level of tertiary education was 47.8%, the majority of gestational age in the second trimester was 41.6% with the majority of pregnancy visits twice at 40.7%. Furthermore, the high level of knowledge is 70.9%, positive attitude is 61.1%, and good behavior is 61.9%. It is recommended that health service personnel be able to facilitate special services for pregnant women by using electronic media to facilitate visits of pregnant women to health services. Keywords: Pregnancy, Covid -19, Knowledge, Attitude, BehaviorAbstract